Age related normogram for antral follicle count in general population and comparison with previous studies. (November 2016) - Bozdag, Gurkan; Calis, Pinar; Zengin, Dila; Tanacan, Atakan; Karahan, Sevilay
Abstract: Objective: To construct antral follicle count (AFC) nomogram of general population for every age and to compare our data with previous studies to assess whether available AFC nomograms present any geographical inconsistency. Study design: A prospective cross-sectional study was conducted to document AFC nomogram among women in 20–50 years with regular menstrual bleeding. Patients admitted with hirsutism, menstrual irregularity, diagnosis of current/history of endometrioma and hormonal drug use within the last 6 months were excluded. For the final analysis, a total of 381 eligible women were recruited in which all scanning was performed in the early follicular phase. The 25th, 50th and 75th percentiles were compared with previous nomogram. Results: The mean decrease of AFC in each year was 0.41. Among the age groups, there were no statistical significance between 20–24, 25–29 and 30–34, whereas decline in AFC was obvious after 35 years and beyond. The figures comparing our data and previous studies depicted similar steady decline at 25th, 50th and 75th percentiles. Conclusion: The current age related nomogram presented a steady decline in AFC that became significant after 35 years in otherwise healthy women with regular menstrual bleeding. Those percentiles might be used as a reference guide to point out the current status of ovarian reserve for a given woman. Additionally, producing nomogram might enforce using percentiles instead of constant thresholds to define various medical conditions such as polycystic ovarian morphology or diminished ovarian reserve. However, longitudinal data with larger sample size are still needed for the validation of those percentiles.